Integrasi Layanan Bimbingan Konseling Islami dalam Pembentukan Karakter dan Akhlak Peserta Didik - Ainur Rofiq (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2025)
This study aims to analyze the role of guidance and counseling (BK) teachers in shaping students’ moral character in Islamic educational institutions. The research is motivated by the increasing moral decline among students, which demands the proactive role of BK teachers in fostering akhlaqul karimah through Islamic-based counseling services. This study employs a qualitative approach using the library research method by reviewing scientific sources such as books, SINTA- and Scopus-indexed journal articles, and official documents related to Islamic education. Data were analyzed using content analysis to interpret conceptual meanings derived from various theories and previous findings. The results indicate that the role of BK teachers in moral formation includes three main dimensions: preventive, curative, and developmental. BK teachers function not only as problem solvers but also as moral educators and spiritual role models who help students develop self-awareness, moral responsibility, and internalized Islamic values. Theoretically, this study contributes to the development of an Islamic value-based counseling model, while practically, it encourages strengthening counseling services in madrasahs. However, this study is limited to conceptual analysis and thus recommends further empirical research to examine the effectiveness of Islamic counseling in improving students’ moral character in real educational settings.